Circulating and Adipose Tissue miRNAs in Women With Polycystic Ovary Syndrome and Responses to High-Intensity Interval Training - Lionett, Sofie; Kiel, Ida A.; Camera, Donny M.; Vanky, Eszter; Parr, Evelyn B.; Lydersen, Stian; Hawley, John A.; Moholdt, Trine (Frontiers in Physiology, 2020)
MicroRNAs (miRNAs) are small non-coding RNAs that regulate gene expression post-transcriptionally. In women with polycystic ovary syndrome (PCOS), several miRNAs are differentially expressed compared to women without PCOS, suggesting that miRNAs may underpin the pathophysiology of this condition. Exercise training modulates miRNA abundance and is recommended as a primary lifestyle intervention for women with PCOS. Accordingly, we measured the expression of eight circulating miRNAs selected a priori along with miRNA expression from gluteal and abdominal adipose tissue (AT) in 12 women with PCOS and 12 women matched for age and body mass index without PCOS (Non-PCOS). We also determined the miRNA expression “signatures” before and after 16 weeks of high-intensity interval training (HIT) in 42 women with PCOS who were randomized to either: 1) Low-volume HIT (LV-HIT, 10 × 1 min work bouts at maximal, sustainable intensity, n=13); 2) High-volume HIT (HV-HIT, 4 × 4 min work bouts reaching 90-95% of maximal heart rate, n=14); or 3) Non-exercise control (Non-Ex, n=15). Both HIT groups trained 3 times/week for 16 weeks. miRNAs were extracted from plasma, gluteal and abdominal AT, and quantified via a customized plate array containing eight miRNAs associated with PCOS and/or exercise training responses. Basal expression of circulating miRNA-27b (c-miR-27b), implicated in fatty acid metabolism, adipocyte differentiation and inflammation, was 1.8-fold higher in women with compared to without PCOS (P=0.006) despite no difference in gluteal or abdominal AT miR-27b expression. Only the HV-HIT protocol increased peak oxygen uptake (VO2peak L/min; 9%, P=0.008). In LV-HIT, but not HV-HIT, the expression of c-miR-27b decreased (0.5-fold, P=0.007). Despite gains in cardiorespiratory fitness, HV-HIT did not alter the expression of any circulating, gluteal or abdominal AT miRNAs in women with PCOS. We conclude that women with PCOS have a higher basal expression of c-miR-27b compared to women without PCOS and that 16 weeks of LV-HIT reduces the expression of this miRNA. Intense exercise training had little effect on the abundance of the selected miRNAs within the subcutaneous adipose tissue depots in women with PCOS.